Les enseignants à l’épreuve de la diversification des élites. Ressorts d’engagement et travail normatif autour du dispositif d’ouverture sociale d’une Grande école - Johan Giry (Cahiers de la Recherche sur l'Education et les Savoirs)
Since the early 2000s, affirmative action policies have emerged in the field of France’s Grandes Écoles as a means to promote equal chance of access to these establishments for high school students. Through a study on one of these policies – the “PEI” policy of one Institut d’Études Politiques – we first show the ways in which these policies rely on the normative work of the teachers involved, both in their functioning and their effects. The meaning teachers attribute to the PEI policy is closely related to the more general transformation of the profession. Afterwards, we demonstrate how the ways in which teachers mobilize the latitude at their disposal to accommodate the PEI lead them to minimize the compensatory dimension of the policy, in favor of a social division of labor based on the groups of pupils involved. Lastly, we highlight the tensions in their relations with the people in charge of the PEI brought upon by such an appropriation, thereby revealing the co-presence of distinct and sometimes contradictory representations of the policy’s relevance and purposes.